2012
DOI: 10.3357/asem.3330.2012
|View full text |Cite
|
Sign up to set email alerts
|

Professional Aircrews’ Attitudes Toward Infectious Diseases and Aviation Medical Issues

Abstract: There were sizable disparities between aircrew flying for U.S. regional, European mainline, and large corporate aviation departments with respect to self-grounding when ill and routinely receiving a seasonal influenza vaccination. All study groups reported a pressing need for enhanced anonymous access to current ID and medical information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Many studies also failed to include the flight crew in the contact tracing, although a previous study showed that many crew members were flying while sick. 58 …”
Section: Discussionmentioning
confidence: 99%
“…Many studies also failed to include the flight crew in the contact tracing, although a previous study showed that many crew members were flying while sick. 58 …”
Section: Discussionmentioning
confidence: 99%
“…For example, Mangili et al [ 22 ] reported that cabin crew frequently fly when ill and typically have low vaccination rates. Substantial disparities exist between aircrews flying for U.S. regional carriers and European flag carriers relating to self-declaration when ill and routine influenza vaccination, with the rate of annual influenza vaccination ranging between 21 and 27% among aircrew [ 25 ].…”
Section: Introductionmentioning
confidence: 99%